Wild leafy vegetable use and knowledge across multiple sites in Morocco: a case study for transmission of local knowledge? - Powell, B.; Ouarghidi, A; Johns, T; Tattou, M.I; Eyzaguirre, Pablo B. (Springer, 2014)
There are few publications on the use and diversity of wild leafy vegetables (WLVs) in Morocco. In order to address this gap, we conducted ethnobotanical field work in Taounate, Azilal and El House regions. Ethnobotanical collections, free listing, qualitative interviews and a 7 day food frequency questionnaire. More than 30 species in 23 genera of WLV were identified. Of these 4 had not previously recorded as WLVs used in Morocco in the literature. WLVs were used by 84% of households surveyed in Taounate (N = 61, in March 2005), and were used up to 4 times a week. Qualitative data revealed both positive and negative perceptions of WLVs and detailed knowledge about preparation among women. The greatest diversity of WLV knowledge and use was in the Rif Mountains (Taounate). There was significant variation in nomenclature and salience of WLVs, not only between regions, but also between villages in the same region. Within the same region (or even village) different local names were used for a given species or genus, and different species were identified by the same local name (including species from different botanical families). Data showed greater overlap in knowledge among villages using the same market. We believe the results suggest that markets are important sites for WLV knowledge transmission.